2011
DOI: 10.1162/jocn.2010.21542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selective Attention on Syntax Processing in Music and Language

Abstract: Abstract■ The present study investigated the effects of auditory selective attention on the processing of syntactic information in music and speech using event-related potentials. Spoken sentences or musical chord sequences were either presented in isolation, or simultaneously. When presented simultaneously, participants had to focus their attention either on speech, or on music. Final words of sentences and final harmonies of chord sequences were syntactically either correct or incorrect. Irregular chords eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 73 publications
7
38
1
Order By: Relevance
“…These electrophysiological potentials are consistent with the latency and the typical polarity inversion of the scalp-recorded ELAN and ERAN at mastoid leads when referenced to nose electrode (Hahne and Friederici, 1999;Koelsch, 2009;Koelsch et al, 2000;Maidhof and Koelsch, 2011), suggesting that the observed effects represent electrocortical equivalents of the scalp-recorded ELAN and ERAN.…”
Section: Domain-general Resourcessupporting
confidence: 77%
“…These electrophysiological potentials are consistent with the latency and the typical polarity inversion of the scalp-recorded ELAN and ERAN at mastoid leads when referenced to nose electrode (Hahne and Friederici, 1999;Koelsch, 2009;Koelsch et al, 2000;Maidhof and Koelsch, 2011), suggesting that the observed effects represent electrocortical equivalents of the scalp-recorded ELAN and ERAN.…”
Section: Domain-general Resourcessupporting
confidence: 77%
“…The ERAN reflects fast and partly automatic processing of music-syntactic violations based on implicit long-term knowledge about the rule system (that is, the ERAN reflects the processing of violations of schematic expectancies; Maidhof and Koelsch, 2011;Koelsch et al, 2002b;Loui et al, 2005). Thus, the data obtained from amateur musicians (and from good performers) suggest that acquisition of veridical knowledge, and corresponding veridical expectancies, do not influence the fast and partly automatic processing based on implicit knowledge of musical regularities, at least not in the relatively early stages of learning (in our experiment, ten learning trials were employed).…”
Section: Erp Resultsmentioning
confidence: 99%
“…Such application of implicit knowledge appears to be automatic, or at least partially automatic (e.g. Bharucha, 1994), that is, it can be observed even in the absence of voluntarily directed attention: Although the ERAN amplitude can be modulated by attentional factors, the ERAN is evoked even when individuals perform attentiondemanding reading tasks during the perception of music (Koelsch et al, 2002b;Loui et al, 2005) or when their attention is directed to a concurrent auditory stream of linguistic information (Maidhof and Koelsch, 2011). Therefore, the present study used the ERAN as an electrophysiological marker of (partially) automatic syntactic processing based on implicit knowledge (amateur musicians also have explicit knowledge, in addition to implicit knowledge, which might contribute to a larger ERAN amplitude in musicians compared to non-musicians).…”
Section: Introductionmentioning
confidence: 99%
“…However, in this respect the attentional capture account could also be defensible by making the similar assumption that the syntactical properties of the irrelevant speech are not processed when the speech is ignored, thereby explaining why they are unable to determine attention capture. At odds with the latter argument, however, is the finding that syntactical violations within auditory sentences elicit early left anterior negativity in event-related potential studies, regardless of whether the speech is attended or to-be-ignored, which suggests that syntactical processing occurs in a manner invariant of selective attention (Maidhof & Koelsch, 2011). In light of this, perhaps the most logical assumption is that interference arises between the semantic processing of individual word meanings because these a processed prior to the processing of syntax (cf.…”
Section: Implications For Theories Of Semantic Auditory Distractionmentioning
confidence: 99%